ANALISIS BAHAN GALIAN TRAS UNTUK BAHAN BAKU INDUSTRI SEMEN BERDASARKAN SIFAT FISIK DAN KIMIA DI PO. JONI EFENDI, KABUPATEN PADANG PARIAMAN, PROVINSI SUMATERA BARAT - Roofi Anabata Zurdi; Fadhilah Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2021)
PO. Joni Efendi is one of the companies that engaged in tras mining in West Sumatra Province. Tras is a C quarry material that can be used in the cement industry. Tras generally have different levels of compounds, physical properties, and colors in each sediment area. This study aims to analyze tras mining materials in the cement industry based on chemical properties and physical properties to obtain the level of quality of tras related to physical properties and color. The research method used is an applied studies and then analyzed based on the study of existing theories. Data collection techniques from this study began with the study of literature, then the collection of data that includes the sampling of tras from 9 points based on color differences and will be analyzed based on the levels of chemical compounds and also their physical properties. The data analyzed will be compared with tras quality standards according to ASTM C618-92a. After the data was analyzed, the tras level in the research area was sufficient and in accordance with the quality standards of tras according to ASTM C618-92a which is 86.285%, this level has also been able to meet consumer demand in the cement industry. Color differences in tras materials are caused by differences in the levels of compounds Si, Fe,Fe2O3 , moisture content and tras that have the best quality are light brown tras with quality content = 86, 963%, moisture content = 21,30%, and density = 1,99 g/cm3.